2010
DOI: 10.1093/eurpub/ckq030
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol policy in a Russian region: a stakeholder analysis

Abstract: Background: Male life expectancy in the Russian Federation, at 60 years, is the lowest in Europe. Several factors contribute to this situation, but hazardous consumption of alcohol is especially a key factor. Methods: We undertook a stakeholder analysis in a typical Russian region located on the western side of the Urals. Organizations with a stake in alcohol policy in the region were identified by snowball sampling and information on their position and influence on alcohol policy was elicited from interviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…One of the approaches employed by the commission to implement its programmes is the collaboration with key stakeholders who have an interest in, or are affected by the present situation related to HIV/AIDS issue and could play roles in influencing the decision-making and implementation process of HIV/AIDS programmes such as religious and traditional leaders, community leaders and HIV/AIDS working groups at sub-district levels (McCaul, 1999;Varvasovszky and Brugha, 2000;Gil et al, 2010). However, one of the respondents interviewed acknowledged that this approach has not been applied as expected, resulting in the limited involvement of the identified key stakeholders:…”
Section: The Responses To Hiv/aids In Belu Districtmentioning
confidence: 99%
“…One of the approaches employed by the commission to implement its programmes is the collaboration with key stakeholders who have an interest in, or are affected by the present situation related to HIV/AIDS issue and could play roles in influencing the decision-making and implementation process of HIV/AIDS programmes such as religious and traditional leaders, community leaders and HIV/AIDS working groups at sub-district levels (McCaul, 1999;Varvasovszky and Brugha, 2000;Gil et al, 2010). However, one of the respondents interviewed acknowledged that this approach has not been applied as expected, resulting in the limited involvement of the identified key stakeholders:…”
Section: The Responses To Hiv/aids In Belu Districtmentioning
confidence: 99%
“…The authors, however, did not explore how this process might happen, what characteristics a stakeholder should possess (e.g., power, influence), and what methods should be used to reach a more prominent influencing position. Gil et al (2010) explored the context of policy making on alcohol in Russia. Using a detailed stakeholders' analysis, they mapped the stakeholders' influence and interest on alcohol policy as well as their relationships, in a typical Russian region.…”
Section: Smentioning
confidence: 99%
“…Our findings suggest that more effective alcohol policies and treatment services in the region may have added benefits in terms of reducing poor mental health, and studies from other regions have shown that treatment for harmful alcohol use can result in a reduction of symptoms of mental disorders (Baker, et al, 2010;Kelly, Stout, Magill, Tonigan, & Pagano, 2010). However, despite the high levels of harmful alcohol consumption and associated burden of poor mental and physical health, recent government alcohol control policies in the region have been marked by limited ambition, lack of engagement and fragmentation among key actors, whereas the larger alcohol producers have become very influential in blocking action (Gil, Polikina, Koroleva, Leon, & McKee, 2010;Nemtsov, 2011;Roberts, et al, 2012a;WHO, 2011a). Although there have been some price controls implemented in Russia on vodka and price controls proposed in Belarus and Ukraine, more concerted action is still urgently required in the fSU, especially given recent evidence that tax policies are equally effective in deterring alcohol consumption for those with high and lower propensity for alcohol use (Dave & Saffer, 2008).…”
Section: Discussionmentioning
confidence: 99%